The Influence of Work Life Balance and Career Development on Job Satisfaction PT Biro Klasifikasi Indonesia Tanjung Perak Surabaya Branch - Annisa Rizky Wijayanti; Endang Iryanti (Universitas KH. Abdul Chalim Mojokerto, 2025)
Employee job satisfaction is one of the important elements that must be considered in a business in terms of human resources. This writing is to find out how employee job satisfaction at PT Biro Klasifikasi Indonesia Tanjung Perak Surabaya branch is influenced by work-life balance and career development. This research methodology uses an associative quantitative approach. The study employed a saturation sampling strategy to choose a sample of 46 employees from the PT Biro Klasifikasi Indonesia Tanjung Perak Surabaya branch. With Partial Least Square (PLS-SEM) analysis. The research findings are, at PT Biro Klasifikasi Indonesia Tanjung Perak Surabaya branch, work life balance has a positive and large effect on employee job satisfaction, and career development has a positive and significant effect on employee job satisfaction.